Analisis Efisiensi Ekonomi Usaha Ayam Ras Petelur di Kabupaten Lombok Timur - Muhamad Sarlan; Sulkiah Sulkiah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
East Lombok Regency is the largest egg production center, controlling 35 percent of the total chicken egg production in West Nusa Tenggara Province. However, its contribution is still relatively low compared to other provinces such as Bali and East Java. This study aims to (1) determine the factors that influence the production of laying hen farming businesses, (2) determine the technical efficiency and technical inefficiency of laying hen farming businesses, and (3) determine the allocative and economic efficiency of laying hen farming businesses in East Lombok Regency. The study was conducted in Bagik Payung Village, Tirtanadi Village, Wanasaba Village, and East Lombok Regency, and it was determined purposively based on the largest laying hen population. The research sample was 61 people who were determined simply randomly. The results of the study showed that (1) the factors that had a positive and significant effect on the production of laying hen farming businesses in East Lombok Regency were the number of chickens (X1), concentrate (X2), vitamins and medicines (X6), while the vaccine variables (X7) and labor (X5) had a negative but insignificant effect on laying hen production. (2) The technical efficiency (TE) value obtained an average of 0.951. The laying hen farming business in East Lombok Regency can be said to be almost technically efficient. Meanwhile, the factors that have a positive and significant influence on the level of technical inefficiency are Education Level (Z2) and Livestock Experience (Z3), while age (Z1) and number of dependents (Z4) have a negative and insignificant influence on efficiency. (3) The distribution of allocative efficiency values is in the range of a minimum of 1.062 and a maximum of 1.248. with an average value of 1.184, indicating that the laying hen farming business in East Lombok is not allocatively efficient. While the average value of economic efficiency is 1.125. This value indicates that economically, the laying hen business in East Lombok Regency is not yet efficient.